Automated detection and temporal monitoring of crevasses using remote sensing and their implications for glacier dynamics. Issue 71 (March 2016) - Bhardwaj, Anshuman; Sam, Lydia; Singh, Shaktiman; Kumar, Rajesh
Abstract: Detailed studies on temporal changes of crevasses and their linkage with glacier dynamics are scarce in the Himalayan context. Observations of temporally changing surficial crevasse patterns and their orientations are suggestive of the processes that determine seasonal glacier flow characteristics. In the present study, on a Himalayan valley glacier, changing crevasse patterns and orientations were detected and mapped on Landsat 8 images in an automated procedure using the ratio of Thermal Infrared Sensor (TIRS) band 10 to Optical Land Imager (OLI) shortwave infrared (SWIR) band 6. The ratio was capable of mapping even crevasses falling under mountain shadows. Differential GPS observations suggested an average error of 3.65% and root-mean-square error of 6.32m in crevasse lengths. A year-round observation of these crevasses, coupled with field-based surface velocity measurements, provided some interesting interpretations of seasonal glacier dynamics.